Dynamic Carbon Emission Measurement and Optimal Dispatching of Power Systems Considering Dual-Carbon Targets - Qiang Li; Feng Zhao; Laidong Zhang; Xuecheng Zhang; Juanyu Liu; Ying Chen; Xinyue Li (IEEE Access)
The power sector’s low-carbon transition is essential to reaching the dual-carbon objective since it is a significant source of energy consumption and greenhouse gas emissions. Thus, in order to lower the power system’s carbon emissions while also ensuring the system’s economy and dependability, the study suggests a dynamic carbon emission measurement and optimal dispatching model that considers the dual-carbon goal. Based on the dynamic carbon emission measurement model, the study uses a method for accounting for carbon emissions that accounts for the unpredictability of grid-connected renewable energy sources like solar and wind. The optimal dispatching of the power system is carried out by means of fuzzy parameter theory and demand response modeling. According to the study’s findings, the suggested model might successfully lower the power system’s carbon emissions while enhancing its dependability and economics. After the implementation of demand response, the total generation cost of the power system was reduced from 1.47 million RMB to 1.15 million RMB, and the total carbon emission was reduced from 44,000 tons to 37,000 tons, which significantly improved the operational efficiency and environmental benefits of the system. The power system’s carbon emissions under various operating situations may be better captured by the suggested dynamic carbon emission measuring methodology. In addition to offering a fresh optimization approach for the power system’s low-carbon operation, the study offers technological solutions and theoretical justification for the dual-carbon objective.